Bioethics as a Human Trait of Common Theory of Law and Criminal Law Theory - Drakić, Dragiša; Trajković, Marko (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
What would be common theory of law without its human features? What would be  criminal law theory without its human traits? It would be a mere form of expression of law. What are today’s best examples of the relation between humanity and law? Nowadays there is series of bioethical issues that provide human aspect to jurisprudence and legal practice. Bioethics offers to the law a real opportunity to rebuild its human content, to go beyond the form and follow the path of humanity. Will the law be subordinated to its form and its procedural side, or it will meet human demands? It will depend from lawyers themselves.